Modelos de Matéria e Energia Escuras Alternativos ao Cenário Padrão - Batista, Carlos Eduardo Magalhães (2010)
In this tese we investigate the behavior of TeVeS when the the ratio between the enegy densities ?2 and ?1 is constant in the Einstein frame, where ?2+?1 = ?ef is the energy density efective in the Einstein frame. We have verified TeVeS can geometrize the dark matter in the physical frame, eliminating the dark matter. Then we used a similar procedure in the case of scalar-tensor theories, preserving the ratio constant between the matter energy density and the field energy density in the Einstein frame. The result predict the existence of geometrized dark energy , then it is not necessary a new kind of energy filling the universe to describe the universe acelaration. The third part deal with the possibility of negative energy density filling the universe. Our model with cosmological constant and sclar field is compared with supernovas types Ia and to the 2dFGRS data. The result show that it is possilble to exist negative energy density for the scalar field as well as for the cosmological constant, but it does not allow negative energy density for the matter.